Hak Hadhanah Anak belum Mumayyiz kepada Ayah Kandung dan Kepentingan Terbaik Anak - Muhamad Ulil Albab; M. Imron; Fetri Fatorina (Matan : Journal of Islam and Muslim Society, 2026)
This study analyzes the Purworejo Religious Court Decision No. 67/Pdt.G/2025/PA.Pwr, which grants custody (hadhanah) of a non-mumayiz child to the biological fathera decision that deviates from the normative provisions of Article 105 letter (a) of the Compilation of Islamic Law (KHI). This research is normative legal research employing statutory, case, and conceptual approaches. The results indicate that the judge's primary considerations were the principle of the best interest of the child and maslahah mursalah, taking into account the ongoing domestic conflict, the parties' agreement in mediation, and the effort to maintain the child's environmental stability. Although textually contradictory to the KHI, this decision can be philosophically justified through the maqashid al-shari'ah approach (protecting the child's soul and progeny) and is in line with the Child Protection Law, which prioritizes the child's best interests. However, this decision has complex implications for gender equality; on one hand, it deconstructs the stereotype of exclusive female caregiving, but on the other hand, it potentially overlooks the early-age child's developmental need for maternal attachment. This study concludes that the decision represents the dynamic evolution of Islamic family law in Indonesia, which is beginning to adopt a substantive approach oriented towards child welfare, though it requires strengthening aspects of parenting capacity assessment and post-decision monitoring mechanisms.